2016
DOI: 10.1111/een.12345
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillar assemblages on Chusquea bamboos in southern Ecuador: abundance, guild structure, and the influence of host plant quality

Abstract: 1. Information on the guild structure of foliage‐associated tropical insects is scarce, especially as caterpillars are mostly considered only as herbivores feeding on living leaves. However, many caterpillar species display alternative trophic associations, feeding on dead or withered leaves or epiphylls (‘non‐herbivores’). 2. To determine the contribution of these non‐herbivores, caterpillar communities associated with Chusquea Kunth (Poaceae) in the Andes of southern Ecuador were investigated. Caterpillars w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…One needs to consider, however, that certain larvae abandon their host-plants searching for a hidden resting place during daytime and mature larvae often leave their food-plant in the last days before pupation looking for a suitable pupation site, sometimes far from their feeding plants. Moreover, in particular in rainwood forests "alternative feeders" may use epiphytes, lianas, lichens, algae, fungi or mosses [14,15], and in our fogging approach pitfalls are possible through collateral fogging of larvae from neighboring trees. Gut content analysis can shed light on true feeding biology.…”
Section: Discussionmentioning
confidence: 99%
“…One needs to consider, however, that certain larvae abandon their host-plants searching for a hidden resting place during daytime and mature larvae often leave their food-plant in the last days before pupation looking for a suitable pupation site, sometimes far from their feeding plants. Moreover, in particular in rainwood forests "alternative feeders" may use epiphytes, lianas, lichens, algae, fungi or mosses [14,15], and in our fogging approach pitfalls are possible through collateral fogging of larvae from neighboring trees. Gut content analysis can shed light on true feeding biology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, due to the high relative humidity in the forest understory along the creeks, leaves are very quickly overgrown by epiphylls (lichens, algae, and fungi) and hence not acceptable to many herbivores which predominantly prefer fresh leaves (Coley & Barone, ; Coley, Kursar & Machado, ; Toomey, Roberts & Nelson, ). Recent studies have shown that, in tropical mountain forests, caterpillars that feed on dead plant parts or graze on epiphylls play a very substantial role (Bodner, Brehm & Fiedler, ; Seifert, Lehner, Bodner & Fiedler, ), but it remains to be shown how important these particular caterpillar guilds are in tropical lowlands. Furthermore, the moist microclimate of the creek forests might facilitate the activity and spread of pathogens, thereby increasing early life stage mortality and finally leading to a lower moth abundance (Hilt, Brehm & Fiedler, ; Intachat, Holloway & Staines, ): (b) Lower plant species richness at creek sites might constrain moth species richness.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested in Stein et al (2014), habitat heterogeneity might be more important for certain herbivores than climatic or topographical heterogeneity since different clades of moth species have developed distinct biological features to cope with environmental factors such as temperature (Braga and Diniz, 2015). By contrast, arctiinae moths comprise a speciose clade of which a large amount of caterpillar species are not classical herbivores as they feed on dead or withered leaves or epiphylls (Bodner et al, 2015;Seifert et al, 2016). Therefore, it is not surprising that neither topographical nor texture metrics as proxies for habitat heterogeneity (dominated by tree crowns) were able to model the species richness of arctiinae moths successively.…”
Section: Species Richness and Habitat Structurementioning
confidence: 99%